2023
DOI: 10.2147/dmso.s434990
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of the Pandemic with Covid-19 in the Glycemic Control of People with Type 2 Diabetes

Adriana Gherbon,
Mirela Frandes,
Marioara Nicula-Neagu
et al.

Abstract: Introduction The COVID-19 lockdown influenced the glycemic control and other metabolic parameters in people with type 1 and 2 diabetes mellitus. Objective To study the effects of COVID-19 lockdown on glycemic control in people with type 2 diabetes mellitus (T2DM). Material and Methods Our study group included 120 Romanian people with T2DM from both urban and rural areas. We employed a structured questionnaire with multiple-choice to collect d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The findings of the study shed light on the impact of the pandemic-related restrictions on the management of T2DM, including the influence of stress, anxiety, and lifestyle changes on glycemic control. 1 …”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the study shed light on the impact of the pandemic-related restrictions on the management of T2DM, including the influence of stress, anxiety, and lifestyle changes on glycemic control. 1 …”
Section: Dear Editormentioning
confidence: 99%
“…The findings of the study shed light on the impact of the pandemic-related restrictions on the management of T2DM, including the influence of stress, anxiety, and lifestyle changes on glycemic control. 1 The study's observation that people with T2DM treated with oral antidiabetics demonstrated better glycemic control compared to those treated with insulin therapy is particularly noteworthy. Additionally, the study highlights the challenges faced by T2DM patients in maintaining a balanced lifestyle and managing their disease during the pandemic.…”
mentioning
confidence: 99%